PUBLIC OPINION REGARDING THE IMPLEMENTATION OF RESTORATIVE JUSTICE ON COMPENSATION SANCTIONS AS AN ALTERNATIVE TOIMPRISONMENT FOR THE CRIME OF DEFAMATION - Hulman Panjaitan; Inri Januar; Petrus Irwan Panjaitan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the eyes of the public, defamation is seen as resulting in damage such as tarnishing one's reputation, including honor. As a criminal act, defamation is regulated from Article 310 to Article 321 of the Criminal Code and Law of the Republic of Indonesia No. 11 of 2008 concerning Information and Electronic Transactions in Article 27 paragraph 3 and Article 45 paragraph 1, which has been amended by Law of the Republic of Indonesia No. 19 of 2016 on amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions. According to these laws, there are clear criminal imprisonment sanctions for offenders, but current public sentiment does not favor this, and the state desires this matter to be resolved through Restorative Justice, as stipulated in the Indonesian National Police Regulation Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, the Republic of Indonesia Attorney General Regulation Number 15 of 2020 regarding the termination of prosecution based on restorative justice, and the decision of the Director General of the General Courts on the Implementation Guidelines of Restorative Justice (restorative justice) Number 1691/DJU/SK/PS.00/12/2020. From the research findings, it is evident that the majority of the public agrees with the application of Restorative Justice by having the offender compensate the victim for damages, usually in the form of a monetary amount agreed upon by the offender and the victim.